Experimental Models of Developmental Hypothyroidism - Argumedo, G. S.; Sanz, C. R.; Olguín, H. J. (Hormone and Metabolic Research, 2012)
Hypothyroidism is a systemic disease resulting from either thyroid gland’s anatomical and functional absence or lack of hypophyseal stimulation, both of which can lead to deficiency in thyroid hormone (TH) production. TH is essential for human and animal development, growth, and function of multiple organs. Children with deficient TH can develop alterations in central nervous system (CNS), striated muscle, bone tissue, liver, bone marrow, and cardiorespiratory system. Among the clinical outlook are signs like breathing difficulty, cardiac insufficiency, dysphagia, and repeated bronchial aspiration, constipation, muscle weakness, cognitive alterations, cochlear dysfunction, reduced height, defects in temperature regulation, anaemia, jaundice, susceptibility to infection, and others.Experimental and clinical studies have shown that TH is very essential for normal brain development. Other research work based on mice pointed out that a reduced level of TH in pregnant mother leads to congenital hypothyroidism in animal models and it is associated with mental retardation, deep neurologic deficiency that impacts on cognitive, learning, and memory functions. The principal experimental model studies that have focused on hypothyroidism are reviewed in this study. This is important on considering the fact that almost all animal species require thyroid hormones for their metabolism.
Keywords: hypothyroidism; animal models; thyroid gland